PENGARUH CAPITAL ADEQUACY RATIO (CAR) TERHADAP HARGA SAHAM DI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BUSA EFEK INDONESIA PERIODE 2008-2017 - WIWI WARSIATI WIWI WARSIATI (POLITEKNIK PIKSI GANESHA, 2019)
This study aims to find out and study the effect of variables, car, on the stock prices of banking companies listed on the stock exchange in the period 2008 - 2017. the data used is secondary data in the form of annual data taken from the annual reports of each bank, bni, mandiri, btn, and bri, this research is a descriptive and verification method. while the data analysis technique used is analysis based on the data obtained, namely regression analysis and multiple linear correlation, and to determine whether or not the relationship of research variables can simultaneously use multiple correlations. where for hypothesis testers the author uses the t test for partial hypotheses, while for testing f uses the simultaneous hypothesis test. from the results of the study it can be concluded that the car, has an influence on stock prices. where the magnitude of the coefficient of determination car, with a stock price of 0.776 this shows the amount of contribution between car, with a stock price of 67.6% besides the significance level between car, the stock price of 0.002 <0.050 ho is rejected which means that there is a significant influence simultaneous between capital adequacy ratio (car), to stock prices